1996
DOI: 10.1074/jbc.271.14.7978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Pax-2 Binding Sites by Chromatin Precipitation

Abstract: The Pax genes encode a family of developmental transcription factors that bind to specific DNA sequences via the paired domain and are necessary for the morphogenesis of a variety of tissues. The murine Pax-2 gene, through alternative splicing, encodes two nuclear proteins, Pax-2A and Pax-2B, which are transiently expressed during the differentiation of specific neural cell types and early kidney formation. In order to identify potential in vivo Pax-2 target sequences, chromatin from embryonic neural tube was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 60 publications
2
36
0
Order By: Relevance
“…Consistent with the similar binding affinity of Pax-2A and Pax-2B for the isolated G3 and G1 elements, both isoforms transactivated G3Ϫ31Glu and G1Ϫ31Glu to a similar extent. Our data are consistent with previous reports observing similar binding and transactivation of Pax-2A and Pax-2B on a Pax-2 consensus element and on three recognition sites identified by chromatin precipitation (6,43). The role of the 23-amino acid insertion in Pax-2A versus Pax-2B ( Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the similar binding affinity of Pax-2A and Pax-2B for the isolated G3 and G1 elements, both isoforms transactivated G3Ϫ31Glu and G1Ϫ31Glu to a similar extent. Our data are consistent with previous reports observing similar binding and transactivation of Pax-2A and Pax-2B on a Pax-2 consensus element and on three recognition sites identified by chromatin precipitation (6,43). The role of the 23-amino acid insertion in Pax-2A versus Pax-2B ( Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Pax-2 transcriptionally activates the Wilms tumor suppressor gene WT1, Engrailed 2, and, cooperatively with homeodomain proteins, the Pax-5 enhancer (45)(46)(47). In addition, two Pax-2 target genes with yet unknown function have been identified by chromatin precipitation using mouse embryonic spinal cord (43). Here we demonstrate that Pax-2 is expressed in the endocrine pancreas and that it transactivates the glucagon gene promoter through two cis-acting sequences, G1 and G3.…”
Section: Discussionmentioning
confidence: 72%
“…Morgenstern et al 13 showed cross-reactivity between commercially available antibodies raised against PAX5 and PAX2. Phelps and Dressler 18 and Gilmore and Dewar 19 also reported cross-reactivity between PAX2 and PAX5 antibodies.…”
Section: Discussionmentioning
confidence: 95%
“…However, many naturally occurring paired domain recognition sequences identified within candidate target promoters are longer than the consensus sequences defined in vitro, and require a contribution from both subdomains for recognition (14). A clear example of this is seen with Pax-2, where selection from a pool of random oligonucleotides defined a 13-bp consensus lacking a C-terminal subdomain recognition motif (25), whereas the purification of Pax-2-bound complexes from native chromatin defined a 23-bp consensus with recognition motifs for both subdomains (31). Therefore, in some instances, the role of the C-terminal subdomain in DNA recognition by Pax proteins may have been masked by the tendency of the N-terminal subdomain to dominate over the C-terminal subdomain in standard in vitro selection protocols.…”
Section: Discussionmentioning
confidence: 99%